Participatory mapping in Papua New Guinea - Hoover, Jamie D., author (Colorado State University. Libraries, 2022)
This record contains supplemental material associated with a participatory mapping project conducted in Papua New Guinea in 2014, including: a summary of the village history, tribal structure, structured and unstructured interviews, and participatory mapping activities discussed in 2011; an overview of other participatory mapping activities conducted in 2014 and some reflections on aspects of the process; questions and scenarios used for the social and environmental impacts workshop; and two videos documenting the project.

Youtube video link for livelihood video made by village: Kamiali Lifestyle Video (English) https://www.youtube.com/watch?v=P7ct7GI-fJk.

Youtube video link on how the participatory video was created: Kamiali Lifestyle Video (English) https://www.youtube.com/watch?v=P7ct7GI-fJk.
ZIP file includes a reflection document with supporting materials and a readme file.
Keywords: participatory mapping; Papua New Guinea; Kamiali; climate change